Analysis of four categories of environmentally friendly building assessment (case study: Ministry of Energy and Mineral Resources, Jakarta) - Rahardjo, Nurul Asmarani Damayanti; Chadirin, Yudi; Karlinasari, Lina (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2023)
The Chairul Saleh Building or the Secretariat General Office Building has implemented the Energy Management Program since 2016. In this study, an assessment was carried out based on the GBCI environmental assessment tool, especially for aspects of land use, energy efficiency and conservation, water conservation, and building environmental management aspects. The requirement analysis to get a green predicate is provided by points assessment which fullfillment the standard. Chairul Saleh building has implemented 10 of the 16 points in Appropriate Site Development category. Energy efficiency and conservation, Chairul Saleh building has implemented 29 of the 36 maximum points. Water Conservation category managed to get 5 out of 20 maximum points, while Building Environmental Management managed to get 11 out of 13 points, Material Resource and Cycle get 8 out of 12 points, Indoor Health and Comfort, get 9 out of 20 points, which was determined in the GBCI greenship rating tools for existing building. The result revealed that in the total value of Chairul Saleh Building was 72 points, it meants achived the Gold certification. Based on the rating set by the GBCI greenship, the Chairul Saleh building is currently awarded a Gold rating for its ability to apply the green building standard.